The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s1516-89132003000100008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tetracycline in the hepatic and renal development of rat's offspring

Abstract: This study aimed on evaluating the possible effects of tetracycline administered to rats on the tenth day of pregnancy, on kidney and liver development of their offspring. The liver showed vacuolization, necrosis, inflammation and sinusoidal dilatations, more evident in the newborn. Mitosis, early increase of Kupffer cells population and hipertrophy of hepatocytes with greater synthesis of glycogen were present on the tenth and twentieth days of life. The kidney showed slight tubular vacuolizations and necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In contrast, both the mother and the baby cannot be harmed by the inadequate treatment of infections. [ 47 ] The present results showed that fetal liver from both treated groups revealed degeneration of hepatic tissue, fatty degeneration, congested central vein, necrosis, and lymphocyte invasion. In addition, the liver of the fetuses showed fatty changes, hemolysis of the blood in sinusoidal spaces, and central vein dilatation with focal hemosiderosis, necrosis, and pyknotic nuclei.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In contrast, both the mother and the baby cannot be harmed by the inadequate treatment of infections. [ 47 ] The present results showed that fetal liver from both treated groups revealed degeneration of hepatic tissue, fatty degeneration, congested central vein, necrosis, and lymphocyte invasion. In addition, the liver of the fetuses showed fatty changes, hemolysis of the blood in sinusoidal spaces, and central vein dilatation with focal hemosiderosis, necrosis, and pyknotic nuclei.…”
Section: Discussionmentioning
confidence: 50%
“…Another report showed that TC can cause chromosomal abnormalities. [ 47 ] In addition, the presence of mitochondrial rich placenta during pregnancy elevates oxidative stress [ 53,54 ] and alters many physiological and metabolic functions. [ 55 ] Over and above this, Sekhon et al [ 56 ] demonstrated that oxidative stress influences multiple physiological processes, from oocyte maturation to fertilization, embryo development, and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…This may likely cause kidney failure due to prolonged rifampicin treatment of tuberculosis, as is clearly seen in our findings. [44] ; reported that rat offspring from parents that receive antibiotic treatment reveal some symptoms of tubular vacuolation and necrosis, and these symptoms are more pronounced in the newborn rats, although some signs of tubular restoration are also seen at 10 and 20 days after treatment. Our result regarding the rifampicin plus stem cell-treated kidney showed an apparently normal histological architecture of renal corpuscle with a well-formed glomerular tuft surrounded by Bowman's space.…”
Section: Discussionmentioning
confidence: 99%
“…11 Toxicity of TCs has proven by long use of this antibiotic or as high dose responses in which kidney and liver are seriously affected. [12][13][14] In their studies, they concluded that the renal side effects of tetracycline showed an increase in Fanconi's syndrome and blood urine nitrogen (BUN). In patients with pre-existing renal impairment, tetracycline may cause azotemia, hyperphosphatemia, and acidosis.…”
Section: Toxicity and Side Effects Of Tetracycline Antibioticmentioning
confidence: 99%